INFLUENCE OF SOWING SCHEMES AND PLANT DENSITY ON PRODUCTIVITY AND AVERAGE FRUITS WEIGHT OF THE TOMATO CV. LYANA - P. M. Ahmedova (Овощи России)
The advantage of the wide-band and stripped scheme of sowing of the early-ripening tomato cultivar Lyana in non-seedling culture is shown.